Identification of Heterotic Groups and Patterns Based on Genotypic and Phenotypic Characteristics Among Rice Accessions of Diverse Origins - Hussain, Izhar; Ali, Sajid; Liu, Wuge; Awais, Muhammad; Li, Jinhua; Liao, Yilong; Zhu, Manshan; Fu, Chongyun; Liu, Dilin; Wang, Feng (Frontiers in Genetics, 2022)
Identification of the right parental combinations to maximize the heterosis is the major goal of hybrid breeding, which could be achieved through identification of heterotic groups. The main objective of this study was to identify promising heterotic groups for future rice breeding programs. A collection of 359 rice genotypes of diverse origins of China and abroad, comprised of inbreds, maintainers, restorers and, TGMS line were genotyped, using 10K SNP chip. The SNP dataset was subjected to genomic analyses for estimation of genetic divergence and diversity. Significant variations were observed in the germplasm with the identification of six different genetic groups. These lines were assigned to the genetic groups independent of their origin. Taking an account of commercially used heterotic groups present in each cluster, 03 CMS lines and 14 inbred and restorer lines with moderate to high genetic distances selected from five heterotic patterns, were crossed and obtained 42 F1 hybrids. Fourteen hybrids were found with significant maximum mid and better parent heterosis viz. TaifengA × Guang122, TaifengA × Wushansimiao and TaifengA × Minghui63 for earliness; Guang8A × Huazhan for dwarf stature; and Guang8A × Huanghuzhan-1, TaifengA × Yuexiangzhan, Guang8A × Minhui3301, TianfengA × Guang122, Guang8A × Yahui2115, TianfengA × Huanghuazhan, TianfengA × Minghui63, TianfengA × Minhui3301, TaifengA × Gui99 and Guang8A × Yuenongsimiao for yield and yield related traits. Mid-parent and better-parent heterotic F1 hybrids was in positive correlation with the genetic distances as that manifested by commercially used heterotic groups, encouraging the use of genotypic data for identification of heterotic groups. The information should also be useful for the development of early maturing, lodging resistant and high yielding commercial hybrids and cultivars in future heterosis breeding programs.